Dispensing hope: leveraging distribution boxes to enhance low-barrier access to naloxone in healthcare settings - Nycole Kothe; Angela Gray; Sarah Guthrie; Michael Londner (Harm Reduction Journal)
Abstract Background West Virginia, often regarded as the epicenter of the opioid epidemic, has consistently recorded the nation’s highest rates of opioid overdose deaths. The Eastern Panhandle, which includes Berkeley, Morgan, and Jefferson counties, mirrors this trend, with Berkeley County’s overdose death rate in 2020 exceeding triple the national average. Recent data, however, indicates a promising 37% decrease in overdose deaths in Berkeley County over a 12-month period ending August 2024, and a statewide decrease of 27.9%. This decline is suspected to be attributed to enhanced access to naloxone and medications for opioid use disorder, supported by community collaboration. Despite these gains, barriers persist for at-risk populations, necessitating strategies such as over-the-counter naloxone availability. Methods The implementation of naloxone distribution boxes in healthcare settings, initiated in Berkeley Medical Center’s emergency department, marks a significant advancement. These boxes, accessible at all times and stocked with OTC (over the counter) naloxone kits, were placed in visible areas of the building vestibule to increase community access to naloxone. Results: Over a six-month period, these boxes distributed 2,383 naloxone kits, significantly surpassing physician-ordered distributions of 17 kits over the same period. Conclusion: Distribution boxes allowed for delivery of large quantities of naloxone compared to the physician-ordered distributions. Future efforts aim to expand naloxone availability in community settings to sustain and further reduce overdose fatalities.